2008
DOI: 10.1371/journal.pone.0003403
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Survey of the Quality of Antimalarials in Retail Outlets in Tanzania

Abstract: IntroductionRetail pharmaceutical products are commonly used to treat fever and malaria in sub-Saharan African countries. Small scale studies have suggested that poor quality antimalarials are widespread throughout the region, but nationwide data are not available that could lead to generalizable conclusions about the extent to which poor quality drugs are available in African communities. This study aimed to assess the quality of antimalarials available from retail outlets across mainland Tanzania.Methods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 14 publications
0
49
1
Order By: Relevance
“…Only four studies used random sampling methods, in which investigators collected samples from outlets that were randomly chosen from a complete or registered list or outlets in a defined area 16 17 19 22. Information on the person collecting the samples was provided by 12 studies 15 17–23 25–28.…”
Section: Resultsmentioning
confidence: 99%
“…Only four studies used random sampling methods, in which investigators collected samples from outlets that were randomly chosen from a complete or registered list or outlets in a defined area 16 17 19 22. Information on the person collecting the samples was provided by 12 studies 15 17–23 25–28.…”
Section: Resultsmentioning
confidence: 99%
“…(15), the prevalence of substandard/counterfeit antimicrobials varied from 10% to more than 50% in some studies (2,7,38,79,80), whereas in another report it was 28.5% (range, 11 to 48%) and was similar in developing countries (22 to 38%). In the latter review, out of a total of 44 identified studies, only 15 studies were included in the analysis based on quality criteria (59), four used random sampling methods (7,28,81,82), and only one included sample size estimates (81). Packaging analysis of the collected samples was performed in only two studies from Southeast Asia (40,58).…”
Section: Counterfeit Drugs Have Been Reported Worldwidementioning
confidence: 99%
“…Numerous antibiotics have been reported to have low quality (76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86) (Tables 4 and 5). In a recent literature review, out of 163 counterfeit antibiotics detected in the world until 2009, 50% were beta-lactams, 12% quinolones, 11% macrolides, lincosamides, and synergistines, 7% cyclins, and 20% other antibiotics (17).…”
Section: Antibacterial Agentsmentioning
confidence: 99%
“…However, due to incorrect storage, inadequate handling and improper transportation, their quality may deteriorate rapidly to the extent that by the time they reach the street vendors, they are already as good as impotent products. Several studies have reported how heat-sensitive medicines, notably, vaccines, antibiotics and anti-malaria products have been transported and stored in inappropriate conditions leading them to degrade [62,66,83,84].…”
Section: International Trade -On the Brink Of Changementioning
confidence: 99%